Answer:
11
Step-by-step explanation:
6 + (8 ÷ 2) - 2 + (4 - 1) =
6 + 4 - 2 + 3 =
11
have a nice day! :)
Answer:
Correct answer is B
Step-by-step explanation:
hope it helps ^^
The answer would be A) less than 1,000 Dollars
The average rate of change of <em>f(x)</em> on -3 ≤ <em>x</em> ≤ 3 is given to be
(<em>f</em> (3) - <em>f</em> (-3)) / (3 - (-3)) = -2.5
If <em>f</em> (-3) = 14, then
(<em>f</em> (3) - 14) / (3 + 3) = -2.5
(<em>f</em> (3) - 14) / 6 = -2.5
<em>f</em> (3) - 14 = -15
<em>f</em> (3) = -1